Post-election violent among youth in Kaduna State, Nigeria: A passion to godfathers politics - Bala, Yusuf; Ismail, Mohd Mahadee; Md Nor, Mohd Sabri; Mohd Zain, Mohd Izani (Human Resource Management Academic Research Society, 2023)
Godfather politics is one of the greatest problems Nigeria’s political system is facing, Kaduna State has a history of violent local conflicts over which group should govern the state and the country. This study is especially important for addressing problems that obstruct society’s development because more than 800 of the 1000 fatalities happened in Kaduna. The main objective of this paper is to investigate the problems of post-election violence in relation to the of role Godfather politics in Nigeria. The paper examine the nature, and effect of godfathers in Nigeria’s political arena, and also the reasons for post-election violence in Kaduna State. The study adopts Elite’s theory of democracy which gives a clear explanation about who godfathers politics organized post-election violent protests among youth in Nigeria. The questionnaires were made and distributed using Google Forms to 300 respondents. Using random sampling. The finding shows that majority the of respondents agreed that hate speech by the opposition party was the reason that led to post-election violence, It is therefore recommended that the national assembly should enact laws that strictly prohibit the production importing, exporting, and acquisition of weapons by individuals in Nigeria, particularly politicians.